2017
DOI: 10.3389/fninf.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vivo and Ex Vivo MRI for the Detection of Structural Abnormalities in a Mouse Model of Tauopathy

Abstract: With increasingly large numbers of mouse models of human disease dedicated to MRI studies, compromises between in vivo and ex vivo MRI must be fully understood in order to inform the choice of imaging methodology. We investigate the application of high resolution in vivo and ex vivo MRI, in combination with tensor-based morphometry (TBM), to uncover morphological differences in the rTg4510 mouse model of tauopathy. The rTg4510 mouse also offers a novel paradigm by which the overexpression of mutant tau can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…High resolution MRI were acquired ex vivo using a small animal 7 Tesla Bruker MRI scanner (Neurospin, Saclay, France). The acquisitions were performed post mortem in order to improve sensitivity (Holmes et al, 2017) . The brain was obtained from a 2 month old ferret.…”
Section: Diffusion Mri Datamentioning
confidence: 99%
“…High resolution MRI were acquired ex vivo using a small animal 7 Tesla Bruker MRI scanner (Neurospin, Saclay, France). The acquisitions were performed post mortem in order to improve sensitivity (Holmes et al, 2017) . The brain was obtained from a 2 month old ferret.…”
Section: Diffusion Mri Datamentioning
confidence: 99%
“…MRS studies on several transgenic mouse models of AD demonstrated the reliable longitudinal assessment of neurochemical changes associated with AD pathology [2426,10]. MR imaging studies of rTg4510 transgenic mice showed extensive brain atrophy [10,27,28] alterations in white matter water diffusion [29,30,27], axonal transport deficit [31], vascular reactivity [32], glutamate and chemical exchange saturation transfer (CEST) signals [27] in rTg4510 mice. Elevated mI concentrations in rTg4510 than wild type (wt) mice have also been reported [10].…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Moreover, recent studies have indicated that significant structural differences in nervous tissues can be seen between ex vivo and in vivo preparations with a clear trade-off between these two imaging approaches. 46 Specifically, we analyzed SC microstructural changes in animal ALS using a different animal model (YFP,G93A-SOD1 mice). Results from our MRI segmentation analysis showed that macrostructural alterations in WM can be detected at the symptomatic stage of the disease, demonstrating the particular susceptibility of this CNS tissue to the SOD1 mutation (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This study is a continuation of our previous work using a new line of mice (C57 mice) with a fluorescent reporter in vivo . A growing number of published studies have pointed to differences between ex vivo models and the need to choose the best model for the purpose of each study: ex vivo for precision; in vivo for time course . Moreover, recent studies have indicated that significant structural differences in nervous tissues can be seen between ex vivo and in vivo preparations with a clear trade‐off between these two imaging approaches .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation